2012
DOI: 10.1523/jneurosci.0554-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cholinergic and GABAergic Mechanisms to Direction Tuning, Discriminability, Response Reliability, and Neuronal Rate Correlations in Macaque Middle Temporal Area

Abstract: Previous studies have investigated the effects of acetylcholine (ACh) on neuronal tuning, coding, and attention in primary visual cortex, but its contribution to coding in extrastriate cortex is unexplored. Here we investigate the effects of ACh on tuning properties of macaque middle temporal area MT neurons and contrast them with effects of gabazine, a GABA A receptor blocker. ACh increased neuronal activity, it had no effect on tuning width, but it significantly increased the direction discriminability of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 72 publications
7
47
0
Order By: Relevance
“…It is thus likely that GABAergic BF projections contribute to the effects reported here. In addition, it is probable that GABAergic cortical interneurons also contribute to reliability regulation, based on recent results showing that suppression of parvalbumin GABAergic interneuron activity in rodent V1 decreases response reliability (Zhu et al 2015), and pharmacological GABA blockade in macaque extrastriate visual cortex enhances Fano factors (Thiele et al 2012). Our findings thus argue for an involvement of both cortical and BF GABAergic cells, as well as an important cholinergic contribution to reliability effects, which is most likely mediated by M2 muscarinic ACh receptors.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It is thus likely that GABAergic BF projections contribute to the effects reported here. In addition, it is probable that GABAergic cortical interneurons also contribute to reliability regulation, based on recent results showing that suppression of parvalbumin GABAergic interneuron activity in rodent V1 decreases response reliability (Zhu et al 2015), and pharmacological GABA blockade in macaque extrastriate visual cortex enhances Fano factors (Thiele et al 2012). Our findings thus argue for an involvement of both cortical and BF GABAergic cells, as well as an important cholinergic contribution to reliability effects, which is most likely mediated by M2 muscarinic ACh receptors.…”
Section: Discussionsupporting
confidence: 62%
“…These are highly concentrated on cortical GABAergic dendrites (Erisir et al 2001), providing a potential mechanism for ACh to regulate cortical interneuron activity and enhance response reliability. An alternative explanation for enhanced V1 reliability involves feed-forward effects from the thalamic lateral geniculate nucleus (LGN), as a result of BF projections to the reticular nucleus of the thalamus, as previously discussed (Thiele et al 2012). In fact, it has been observed that spiking reliability in the LGN is also enhanced following BF electrical stimulation (Goard and Dan 2009).…”
Section: Discussionmentioning
confidence: 93%
“…A large body of work addressing the effect of acetylcholine on neural responses was done in anesthetized animals (4,7,14,27), where baseline cholinergic activity is low (28), making it difficult to interpret how the results generalize to more ecologically valid situations. Previous studies also used global stimulation of the basal forebrain (29)(30)(31)(32)(33), a technique that activates the entire population of basal forebrain cell types including cortically projecting cholinergic neurons in addition to GABAergic neurons projecting to cortex (for review, see ref.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous work analyzed the influence of acetylcholine on total correlations (4) or noise correlations (14), it is not clear how these variables alone might influence neural coding (15). Theoretical research indicates that encoding capacity depends on the details of the correlation structure, analyzed in terms of the relationship between signal and noise correlations (12,(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…For example, in the primary visual cortex (V1), costimulation of the classical-and non-classical receptive field (RF) of pyramidal neurons causes an increase in response reliability and sparseness; these effects were associated with increased inhibitory inputs 9 . In the middle temporal visual area, blocking GABAergic inhibition reduces response reliability and direction selectivity of cortical neurons 10 . In the auditory cortex, balanced but delayed inhibition produces precise spike timing of toneevoked cell responses 11 .…”
mentioning
confidence: 99%